Inside Front Cover: Three‐dimensional printed microfluidic mixer/extractor for cell lysis and lipidomic profiling by matrix‐assisted laser desorption/ionization mass spectrometry (View 1/2023). Issue 1 (21st February 2023) - Yang, Zhengdong; Li, Bochao; Stuart, Daniel D.; Cheng, Quan
Abstract : A 3D printed microfluidic device with a micropillar mixer for onchip cell lysis and separation demonstrated with the algae cells. The enriched lipids are loaded onto a microarray for lipidomic profiling by MALDI‐MS to reveal cytotoxicity effect and for disease diagnosis.